Negative interference of icteric serum on a bichromatic biuret total protein assay. - Gupta, Aradhana; Stockham, Steven L. (My University, 2014)
Background: Bilirubin is stated to be a negative interferent in some biuret assays and thus could contribute to pseudohypoproteinemia in icteric samples. Objective: The purpose of the study was to evaluate the magnitude of and reason for a falsely low total protein concentration in icteric serum when the protein concentration is measured with a bichromatic spectrophotometric biuret assay. Methods: Commercially available bilirubin was dissolved in 0.1 M NaOH and then mixed with sera from 2 dogs to achieve various bilirubin concentrations of up to 40 mg/dL (first set of samples) and 35 mg/dL (second set of samples, for confirmation of first set of results and to explore the interference). Biuret total protein and bilirubin concentrations were determined with a chemistry analyzer (Cobas® 6000 with c501 module). Line graphs were drawn to illustrate the effects of increasing bilirubin concentrations on the total protein concentrations. Specific spectrophotometric absorbance readings were examined to identify the reason for the negative interference. Results: High bilirubin concentrations created a negative interference in the Cobas biuret assay. The detectable interference occurred with a spiked bilirubin concentration of 10.7 mg/dL in one set of samples and 20.8 mg/dL in a second set. The interference was due to a greater secondary absorbance reading at the second measuring point in the samples spiked with bilirubin, which possibly had converted to biliverdin. Conclusion: Marked hyperbilirubinemia is associated with a falsely low serum total protein concentrations when measured with a bichromatic spectrophotometric biuret assay. This can result in pseudohypoproteinemia and pseudohypoglobulinemia in icteric serum.
Keywords: Bilirubin; Clinical chemistry; Error; Hypoproteinemia